2023
DOI: 10.1093/infdis/jiad483
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Immunization Products Against Medically Attended Respiratory Syncytial Virus Infection: Generic Protocol for a Test-Negative Case-Control Study

Caren van Roekel,
Eero Poukka,
Topi Turunen
et al.

Abstract: Monitoring the real-life effectiveness of respiratory syncytial virus (RSV) products is of major public health importance. This generic protocol for a test-negative design study aims to address currently envisioned approaches for RSV prevention (monoclonal antibodies and vaccines) to study effectiveness of these products among target groups: children, older adults and pregnant women. The generic protocol approach was chosen to allow for flexibility in adapting the protocol to a specific setting. This protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A limitation of our definition is the uncertainty of the antigenic effect of individual amino acid substitutions on lineages. Hence, whole-genome surveillance together with the study of lineage-phenotype association are essential, as observed in genetic and antigenic characterization in influenza to estimate the effectiveness of immunization ( 47 ). In 2023, recombinant F protein vaccines were approved; as their implementation progresses, we will learn how the vaccines affect viral evolution.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our definition is the uncertainty of the antigenic effect of individual amino acid substitutions on lineages. Hence, whole-genome surveillance together with the study of lineage-phenotype association are essential, as observed in genetic and antigenic characterization in influenza to estimate the effectiveness of immunization ( 47 ). In 2023, recombinant F protein vaccines were approved; as their implementation progresses, we will learn how the vaccines affect viral evolution.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know a priori whether a simple amino acid substitution may have a significant epidemiological impact. Hence, whole genome surveillance and the study of the lineagephenotype association will be essential, as observed in genetic and antigenic characterization in influenza to estimate the effectiveness of immunization (50). Other knowledge gaps include, but are HRSV classification below the subgroup level not limited to, analyzing the association between lineages and the severity of HRSV disease, as well as associations of particular lineages with demographic characteristics of individuals.…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%